Is the Younger the Better? Teaching English to Young Learners in the Indonesian Context - Damayanti, Ika Lestari (EDUCARE, 2008)
ABSTRACT: It is universally acknowledged that learning a second/foreign language, e.g. English, since early childhood would contribute positively to the childâs language acquisition. Native-like pronunciation is one of the favored results gained from this process. This assumption is strongly supported by the Critical Period Hypothesis i.e. a biologically determined period of life when language can be acquired more easily. However, many studies indicate that âthe younger the betterâ in learning English is not necessarily true. Native-like pronunciation and proficiency have been found to be acquired by a learner who started learning English in his adulthood. In regard to this matter, this paper attempts to review a belief âthe younger the betterâ in learning English in the Indonesian context by looking at issues related to optimal age, factors contributing to the success of L2 acquisition, and current practices of teaching English to Young Learners (TEYL) in the Indonesian context.Â KEY WORDS: second language, teaching English to young learners, critical period hypothesis, optimal age, psychosocial context, and learning condition.About the Author: Ika Lestari Damayanti, M.A. is a Lecturer at English Department, Faculty of Art and Language Education (FPBS), Indonesia University of Education (UPI) in Bandung. She could be reached at ikadlovely@yahoo.com.sgHow to cite this article? Damayanti, Ika Lestari. (2008). âIs the Younger the Better? Teaching English to Young Learners in the Indonesian Contextâ in EDUCARE: International Journal for Educational Studies, Vol.1(1) August, pp.31-38. Bandung, Indonesia: Minda Masagi Press owned by ASPENSI in Bandung, West Java; and FKIP UMP in Purwokerto, Central Java, ISSN 1979-7877.Chronicle of the article: Accepted (June 27, 2008); Revised (July 27, 2008); and Published (August 17, 2008).